The role of psychological characteristics in facilitating the pathway to elite performance part 1: Identifying mental skills and behaviors - MacNamara, A.; Button, A.; Collins, D. (The Sport Psychologist, 2010)
Given the complexity of the talent development process, it seems likely that a range of psychological factors underpin an athlete`s ability to translate potential into top-class performance. Therefore, the purpose of part one of this two-part investigation was to explore the attributes that facilitate the successful development of athletes from initial involvement to achieving and maintaining world-class status. Seven elite athletes and a parent of each of these athletes were interviewed regarding their own (their son`s/ daughter`s) development in sport. Data were content analyzed using a grounded theory approach. Although sporting achievement was conceptualized as being multidimensional, psychological factors were highlighted as the key determinants of those who emerged as talented and maintained excellence. Accordingly, we suggest that talent identification and development programs should place greater emphasis on the advancement and application of psychological behaviors at an early stage to optimize both the development and performance of athletes.